Identification of potential therapeutic targets in prostate cancer through a cross‐species approach. Issue 3 (5th February 2018) - Jurmeister, Sarah; Ramos‐Montoya, Antonio; Sandi, Chiranjeevi; Pértega‐Gomes, Nelma; Wadhwa, Karan; Lamb, Alastair D; Dunning, Mark J; Attig, Jan; Carroll, Jason S; Fryer, Lee GD; Felisbino, Sérgio L; Neal, David E
Abstract: Genetically engineered mouse models of cancer can be used to filter genome‐wide expression datasets generated from human tumours and to identify gene expression alterations that are functionally important to cancer development and progression. In this study, we have generated RNAseq data from tumours arising in two established mouse models of prostate cancer, PB‐Cre/Pten loxP/loxP and p53 loxP/lox P Rb loxP/loxP, and integrated this with published human prostate cancer expression data to pinpoint cancer‐associated gene expression changes that are conserved between the two species. To identify potential therapeutic targets, we then filtered this information for genes that are either known or predicted to be druggable. Using this approach, we revealed a functional role for the kinase MELK as a driver and potential therapeutic target in prostate cancer. We found that MELK expression was required for cell survival, affected the expression of genes associated with prostate cancer progression and was associated with biochemical recurrence. Synopsis: Genetically engineered mouse models (GEMM) of human cancers can be used as "biological filters" to identify genes that are important to cancer development and prioritise potential therapeutic targets. The example of MELK in prostate cancer. Comparisons of high‐throughput sequencing data from two GEMM of prostate cancer with human prostate cancer gene expression data revealed that human and murine tumours share common gene expression alterations. Integration of human and murine gene expression data was used to identify potential therapeutic targets in prostate cancer, including the protein kinase MELK. MELK is overexpressed in prostate cancer and associated with poor prognosis. Silencing of MELK or treatment with an inhibitor targeting MELK resulted in induction of apoptosis in prostate cancer cells in vitro and in vivo . Abstract : Genetically engineered mouse models (GEMM) of human cancers can be used as "biological filters" to identify genes that are important to cancer development and prioritise potential therapeutic targets. The example of MELK in prostate cancer.